Liquid crystal polyester film, and metal laminated film and circuit board using same

By controlling the dynamic friction coefficient near the crystallization temperature, the problem of the thermoplastic liquid crystal polyester film prone to slack and wrinkles in blow-molding extrusion molding is solved, and a liquid crystal polyester film with excellent smooth and mechanical characteristics is realized, which is suitable for high-speed communications Circuit substrates, etc.

CN119463432APending Publication Date: 2025-02-18OKURA INDUSTRIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411079820.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the thermoplastic liquid crystal polyester film is prepared by blow molding and extrusion molding, slack and wrinkles are easily generated on the film, making it difficult to obtain a smooth film.

Method used

By controlling the dynamic friction coefficient near the crystallization temperature, it is less than 0.25, and the dynamic friction coefficient near the crystallization temperature is less than 1.25, thereby suppressing the film's sagging and wrinkles.

Benefits of technology

The smoothness of the liquid crystal polyester film prepared in the blow molding extrusion molding method is achieved, with excellent mechanical characteristics, electrical characteristics and heat resistance, and is suitable for applications such as circuit substrates for high-speed communication purposes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463432A_ABST
    Figure CN119463432A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a smooth liquid crystal polyester film which has excellent mechanical characteristics, electrical characteristics, and heat resistance and in which slack and wrinkles of the film are suppressed during extrusion molding such as a blow extrusion molding method; and a metal laminated film and a circuit board which use the film. A liquid crystal polyester-based film which contains a thermoplastic liquid crystal polyester as a main component, and which has a crystallization temperature (Tc) of 180-320 DEG C inclusive and a dynamic friction coefficient ([mu] D1) of 0.25 or less at the crystallization temperature (Tc) + 5 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal polyester film mainly composed of a thermoplastic liquid crystal polyester capable of forming an optically anisotropic molten phase, and a metal laminate film and a circuit board using the film. Background Art

[0002] In recent years, in the field of electronics and electrical equipment, the demand for miniaturization and lightness of equipment has increased, and insulating films with excellent electrical and mechanical properties are required. However, polyimide and polyethylene terephthalate, which are raw materials for existing insulating films, have problems such as insufficient electrical properties in high frequency bands, high hygroscopicity that causes changes in electrical properties and large dimensional changes, making it difficult to achieve films that meet the above requirements.

[0003] Thermoplastic liquid crystal polyesters are attracting attention as materials for flexible printed circuit (FPC) substrates, etc., due to their excellent mechanical properties such as heat resistance and rigidity, chemical resistance, dimensional accuracy, etc., as well as excellent electrical properties (low dielectric constant, dielectric loss tangent) in high frequency bands (GHz band) and low transmission loss in circuits.

[0004] Thermoplastic liquid crystal polyester can be made into a film by various extrusion molding methods. However, in the film made by T-die extrusion molding, the thermoplastic liquid crystal polyester having a rigid molecular structure has the property that the molecules are easily oriented along the flow direction in the molten state, so in the pulling direction (MD direction) and the direction orthogonal thereto (TD direction), the molecular chain orientation shows anisotropy, and therefore, it is difficult to obtain a thermoplastic liquid crystal polyester film with isotropic molecular chain orientation.

[0005] In contrast, the blow extrusion molding method can stretch the molten thermoplastic liquid crystal polyester extruded from the annular die in both the MD and TD directions. Therefore, by appropriately adjusting the blow ratio and controlling the molecular chain orientation, an isotropic thermoplastic liquid crystal polyester film can be easily obtained. Therefore, various studies have been conducted on the use of the blow extrusion molding method when using thermoplastic liquid crystal polyester for film production.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2001-88213

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 2002-240146 Summary of the invention

[0010] In addition, thermoplastic liquid crystal polyester has a high tensile modulus and a low elongation at break, and therefore has a high rigidity. After being formed into a film by a blow extrusion molding method, wrinkles and sagging are easily generated on the film, and it is difficult to obtain a smooth film.

[0011] For example, in the blow extrusion molding method, a molten resin is extruded from an annular slit into a bubble shape, and air or an inert gas is blown into the bubble formed by the molten resin from the inside, thereby expanding and stretching the bubble in the MD direction and the TD direction, and the expanded and stretched bubble is brought into contact with a pair of stabilizing plates inclined so that the downstream sides in the MD direction are close to each other, and the bubble is slowly folded into a flat shape and guided toward a pinch roller, and the bubble is folded into a plane shape by a pair of pinch rollers. In the process of bringing the cylindrical bubble into contact with the stabilizing plate and folding the bubble into a flat shape by the pinch rollers, the geometric straight line distance from the position where the bubble directly contacts the stabilizing plate to the pinch rollers is different for the bubble located at the center of the stabilizing plate and the bubble located at the two ends of the stabilizing plate. Therefore, when the rigidity of the resin is high, the film cannot be deformed when clamped in a plane shape between the pinch rollers, thereby causing slack or wrinkles (longitudinal wrinkles) in the MD direction on the film.

[0012] Therefore, when thermoplastic liquid crystal polyester is formed into a film by blow extrusion molding, it is an effective means to control the resin temperature of the bubble when the bubble is folded into a flat shape between the pinch rolls to a high temperature so as to maintain the shape of the bubble and make the film easy to deform when clamped, thereby suppressing the generation of slack or longitudinal wrinkles on the film. On the other hand, a new problem arises, that is, when the resin temperature of the bubble is controlled until the pinch roll position, the sliding property of the bubble deteriorates, and the friction between the bubble and the stabilizing plate causes crescent-shaped wrinkles (transverse wrinkles) in the TD direction of the bubble, making it difficult to obtain a smooth film.

[0013] The present invention has been made in view of the above problems, and an object of the present invention is to provide a smooth liquid crystal polyester film which has excellent mechanical properties, electrical properties and heat resistance and suppresses film sagging and wrinkles during extrusion molding such as blow extrusion molding.

[0014] The present inventors have conducted intensive research on a smooth liquid crystal polyester film that has excellent mechanical properties, electrical properties, and heat resistance and suppresses film sag and wrinkles during extrusion molding such as blow extrusion molding. As a result, they found that the slippage of the film near the crystallization temperature, which is when the molecular chains of the molten thermoplastic liquid crystal polyester are oriented, significantly changes in the slippage of the thermoplastic liquid crystal polyester near the crystallization temperature, and the slippage deteriorates. In addition, the present inventors found that by controlling the slippage of the film near the crystallization temperature, a smooth liquid crystal polyester film that suppresses sag and wrinkles during extrusion molding such as blow extrusion molding can be obtained, and thus the present invention has been completed.

[0015] According to the present invention, the following solution is provided.

[0016] (1) A liquid crystal polyester film, characterized in that it contains a thermoplastic liquid crystal polyester as a main component, has a crystallization temperature (Tc) of 180°C or higher and 320°C or lower, and has a dynamic friction coefficient (μ) at the crystallization temperature (Tc) + 5°C. D1 ) is less than 0.25,

[0017] (2) A liquid crystal polyester film, characterized in that it contains a thermoplastic liquid crystal polyester as a main component, has a crystallization temperature (Tc) of 180°C or higher and 320°C or lower, and has a dynamic friction coefficient (μ) at the crystallization temperature (Tc) + 5°C. D1 ) and the dynamic friction coefficient (μ) at the crystallization temperature (Tc)-5°C D2 ) of the dynamic friction coefficient (μ D1 / μ D2 ) is less than 1.25,

[0018] (3) The liquid crystal polyester film according to (1) or (2), wherein the thermoplastic liquid crystal polyester comprises at least one selected from the group consisting of constituent units derived from p-hydroxybenzoic acid and constituent units derived from 6-hydroxy-2-naphthoic acid,

[0019] (4) The liquid crystal polyester film according to (1) or (2), wherein the crystallization temperature (Tc) is 220° C. or higher and 300° C. or lower.

[0020] (5) The liquid crystal polyester film according to (1) or (2), characterized in that it contains an amorphous copolyester having a glass transition temperature of 80° C. to 200° C.,

[0021] (6) The liquid crystal polyester film according to (5), wherein the amorphous copolyester comprises a constituent unit derived from a terephthalic acid-based monomer and a constituent unit derived from 1,4-cyclohexanedimethanol,

[0022] (7) The liquid crystal polyester film according to (1) or (2), wherein the liquid crystal polyester film is a blown film.

[0023] (8) A metal laminate film, characterized in that a metal layer is laminated on one or both sides of the liquid crystal polyester film described in (1) or (2),

[0024] (9) A circuit board comprising at least one conductive layer and the liquid crystal polyester film according to (1) or (2).

[0025] In the present invention, a liquid crystal polyester film having a small dynamic friction coefficient near the crystallization temperature and a small change in the dynamic friction coefficient near the crystallization temperature, and having no sags or wrinkles can be obtained. In addition, the liquid crystal polyester film of the present invention has excellent mechanical properties, electrical properties, and heat resistance, and the film is also excellent in smoothness, so the thickness uniformity is also excellent. The metal laminate film obtained by laminating the liquid crystal polyester film and the metal layer has excellent mechanical properties, electrical properties, and reflow solderability, and has a small insertion loss for high-frequency signal transmission, and can be used for laminated boards for circuit substrates suitable for high-speed communication applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a simplified schematic diagram showing an example of a measuring device for the coefficient of dynamic friction in the present invention.

[0027] Description of Reference Numerals

[0028] 1: Weighing sensor

[0029] 2: Pulley

[0030] 3: Sliding parts

[0031] 4: Total mass of sliding parts

[0032] 5: Sample

[0033] 6: Hot plate (table). DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will be described in detail. It should be noted that the present invention is not limited to the following forms, and various forms can be adopted within the scope of achieving the effects of the present invention.

[0035] [Liquid crystal polyester film]

[0036] The liquid crystal polyester film of the present invention is characterized in that it contains a thermoplastic liquid crystal polyester as a main component and has excellent sliding properties near the crystallization temperature. Specifically, as a scheme, the dynamic friction coefficient (μ) of the liquid crystal polyester film at the crystallization temperature (Tc) + 5°C is D1) is less than 0.25. The liquid crystal polyester film having such characteristics has a small dynamic friction coefficient near the crystallization temperature, and therefore, can obtain a smooth film with excellent sliding properties with a stabilizing plate during extrusion molding such as blow extrusion molding, and no relaxation and wrinkles. In addition, when the dynamic friction coefficient near the crystallization temperature is small, wrinkles can be suppressed when the liquid crystal polyester film and the metal foil are heated and pressed (laminated) using a heating roller, etc., thereby obtaining a smooth metal laminated film. It should be noted that, here, the main component means a component with a constituent ratio of 50% by weight or more in the components constituting the film, preferably 60% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0037] Dynamic friction coefficient (μ) of liquid crystal polyester film at crystallization temperature (Tc) + 5°C D1 ) is preferably 0.24 or less, more preferably 0.23 or less, further preferably 0.22 or less, and particularly preferably 0.20 or less. D1 The lower limit of ) is not particularly limited, and is, for example, 0.01 or more, preferably 0.03 or more, and more preferably 0.05 or more. The dynamic friction coefficient (μ D1 ) The method of forming a liquid crystal polyester film that meets the above range is not particularly limited, and examples thereof include: a method of adjusting the type of monomer components, the molar ratio of the monomer components, the degree of polymerization, etc. of the thermoplastic liquid crystal polyester; a method of blending two or more thermoplastic liquid crystal polyesters with different compositions; a method of blending amorphous polymers; a method of adding particles composed of inorganic or organic materials for improving sliding properties. It should be noted that the dynamic friction coefficient (μ D1 ) can be measured by the method described below in accordance with JIS K7125.

[0038] In addition, as another embodiment of the liquid crystal polyester film of the present invention, the dynamic friction coefficient (μ D1 ) and the dynamic friction coefficient (μ) at crystallization temperature (Tc) -5℃ D2 ) of the dynamic friction coefficient (μ D1 / μ D2 ) is less than 1.25. The liquid crystal polyester film having such characteristics has a small increase and change in the dynamic friction coefficient near the crystallization temperature. Therefore, it is possible to obtain a smooth film with a wide process window for film processing during extrusion molding such as blow extrusion molding, excellent sliding properties with a stabilizing plate, and no sag and wrinkles. In addition, when the increase in the dynamic friction coefficient near the crystallization temperature is small, it is possible to suppress the generation of wrinkles when the liquid crystal polyester film and the metal foil are heated and pressed (laminated) using a heating roller, etc., thereby obtaining a smooth metal laminate film. Dynamic friction coefficient ratio (μ D1 / μ D2) is preferably 1.20 or less, more preferably 1.15 or less, further preferably 1.10 or less, and particularly preferably 1.00 or less. D1 / μ D2 The lower limit of ) is not particularly limited, and is, for example, 0.01 or more, preferably 0.03 or more, and more preferably 0.05 or more. The dynamic friction coefficient ratio (μ D1 / μ D2 ) The method of forming a liquid crystal polyester film that meets the above range is not particularly limited, and examples thereof include: a method of adjusting the type of monomer components, the molar ratio of the monomer components, the degree of polymerization, etc. of the thermoplastic liquid crystal polyester; a method of blending two or more thermoplastic liquid crystal polyesters with different compositions; a method of blending amorphous polymers; a method of adding particles composed of inorganic or organic materials that improve sliding properties. It should be noted that the dynamic friction coefficient (μ D1 , μ D2 ) can be measured by the method described below in accordance with JIS K7125.

[0039] The crystallization temperature (Tc) of the liquid crystal polyester film of the present invention is 180°C or more and 320°C or less. If the crystallization temperature (Tc) is within the above range, a smooth film having excellent mechanical properties, electrical properties, and heat resistance, and excellent molding processability, and no slack and wrinkles can be obtained. The upper limit of the crystallization temperature (Tc) is preferably 310°C or less, more preferably 300°C or less, further preferably 295°C or less, and particularly preferably 290°C or less. The lower limit of the crystallization temperature (Tc) is preferably 190°C or more, more preferably 200°C or more, further preferably 210°C or more, and particularly preferably 220°C or more. It should be noted that the crystallization temperature (Tc) of the liquid crystal polyester film is a value measured by a differential scanning calorimeter (DSC). Specifically, the temperature is raised from room temperature to 320-380°C at a heating rate of 10°C / min to completely melt the liquid crystal polyester film, and then the temperature is lowered to 30°C at a cooling rate of 10°C / min. The top of the exothermic peak is taken as the crystallization temperature (Tc).

[0040] The thickness of the liquid crystal polyester film of the present invention is not particularly limited, and is, for example, 0.5 μm to 1000 μm. Considering the operability and productivity of the film, it is preferably 5 μm to 500 μm, more preferably 10 μm to 300 μm, and further preferably 20 μm to 200 μm.

[0041] The tensile strength of the liquid crystal polyester film of the present invention in the flow direction (MD direction) and the width direction (TD direction) is preferably 180MPa or more. The tensile strength is preferably 200MPa or more, more preferably 220MPa or more. The upper limit of the tensile strength is not particularly limited, for example, preferably 500MPa or less, more preferably 400MPa or less, more preferably 350MPa or less. If the tensile strength is within the above range, the laminated board for the circuit substrate suitable for high-speed communication applications is excellent in operability, and the end of the film can be suppressed from being missing or cracked.

[0042] The liquid crystal polyester film of the present invention preferably has low anisotropy in the flow direction (MD direction) and the width direction (TD direction). In detail, the tensile strength F(TD) in the film width direction relative to the tensile strength F(MD) in the film flow direction (i.e., F(TD) / F(MD)) is preferably 0.5 or more and 1.5 or less, more preferably 0.75 or more and 1.25 or less, further preferably 0.85 or more and 1.15 or less, and particularly preferably 0.90 or more and 1.10 or less. If the tensile strength F(TD) in the film width direction relative to the tensile strength F(MD) in the film flow direction is within the above range, the anisotropy of the mechanical and electrical properties of the film is small, and it can be applied to laminated boards for circuit substrates suitable for high-speed communication purposes.

[0043] The dielectric loss tangent of the liquid crystal polyester film of the present invention is preferably 0.0025 or less, the dielectric loss tangent is more preferably 0.0024 or less, further preferably 0.0022 or less, and particularly preferably 0.0020 or less. In addition, the relative dielectric constant of the liquid crystal polyester film of the present invention is preferably 2.0 to 4.0. The relative dielectric constant is more preferably 2.5 to 3.9, more preferably 2.6 to 3.8, and further preferably 2.8 to 3.8. The dielectric properties including the standard dielectric loss tangent and the relative dielectric constant can be measured by the cavity resonator perturbation method.

[0044] [Thermoplastic Liquid Crystal Polyester]

[0045] The thermoplastic liquid crystal polyester used in the present invention is a liquid crystal polyester showing melt anisotropy (a polyester that can form an optically anisotropic melt phase). The property of melt anisotropy can be confirmed by a commonly used polarization inspection method using crossed polarizers. Specifically, melt anisotropy can be confirmed by using a polarizing microscope (manufactured by Olympus Corporation, etc.) to melt a sample placed on a hot stage (manufactured by LINKAM, etc.) and observing at a magnification of 150 times under a nitrogen atmosphere. A liquid crystal resin that shows optical anisotropy when melted is optically anisotropic and is light-transmissive when inserted between crossed polarizers. When the sample is optically anisotropic, for example, polarized light can be transmitted even in a molten static liquid state.

[0046] As a thermoplastic liquid crystal polyester, as long as it is a liquid crystal polyester that can be melt-molded, its chemical composition is not particularly limited, and examples thereof include: a thermoplastic liquid crystal polyester having at least one repeating unit selected from the group consisting of aromatic hydroxycarboxylic acids, aromatic or aliphatic diols, aromatic or aliphatic dicarboxylic acids, aromatic diamines, aromatic hydroxylamines and aromatic aminocarboxylic acids.

[0047] As aromatic hydroxycarboxylic acids, p-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and 4-(4-hydroxyphenyl)benzoic acid can be mentioned. These compounds may have substituents such as halogen atoms, lower alkyl groups and phenyl groups. Among them, p-hydroxybenzoic acid or 6-hydroxy-2-naphthoic acid is preferred. As aromatic or aliphatic diols, aromatic diols are preferred. As aromatic diols, hydroquinone, 4,4'-dihydroxybiphenyl, 3,3'-dimethyl-1,1'-biphenyl-4,4'-diol and their acyl compounds can be mentioned, preferably hydroquinone or 4,4'-dihydroxybiphenyl. As aromatic or aliphatic dicarboxylic acids, aromatic dicarboxylic acids are preferred. As aromatic dicarboxylic acids, terephthalic acid, isophthalic acid and 2,6-naphthalenedicarboxylic acid can be mentioned, preferably terephthalic acid. Examples of the aromatic diamine, aromatic hydroxyamine, and aromatic aminocarboxylic acid include p-phenylenediamine, 4-aminophenol, and 4-aminobenzoic acid.

[0048] The thermoplastic liquid crystal polyester preferably has at least one selected from the group consisting of repeating units represented by the following formulae (1) to (3).

[0049] -O-Ar1-CO-(1)

[0050] -CO-Ar2-CO-(2)

[0051] -X-Ar3-Y-(3)

[0052] In the formula (1), Ar1 represents a phenylene group, a naphthylene group or a biphenylene group.

[0053] In the formula (2), Ar2 represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4).

[0054] In the formula (3), Ar3 represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group.

[0055] -Ar4-Z-Ar5-(4)

[0056] In formula (4), Ar4 and Ar5 each independently represent a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.

[0057] The phenylene group, the naphthylene group, and the biphenylene group may have a substituent selected from the group consisting of a halogen atom, an alkyl group, and an aryl group.

[0058] Among them, the thermoplastic liquid crystal polyester preferably has at least one selected from the group consisting of repeating units derived from aromatic hydroxycarboxylic acids represented by the above formula (1), repeating units derived from aromatic diols represented by the above formula (3) in which both X and Y are oxygen atoms, and repeating units derived from aromatic dicarboxylic acids represented by the above formula (2).

[0059] In addition, as a thermoplastic liquid crystal polyester, it is preferred to have a constituent unit derived from an aromatic hydroxycarboxylic acid, more preferably to have at least one selected from the group consisting of a constituent unit derived from p-hydroxybenzoic acid and a constituent unit derived from 6-hydroxy-2-naphthoic acid, and further preferably to have a constituent unit derived from p-hydroxybenzoic acid and a constituent unit derived from 6-hydroxy-2-naphthoic acid.

[0060] As another preferred embodiment, the thermoplastic liquid crystal polyester more preferably has at least one selected from the group consisting of constituent units derived from 6-hydroxy-2-naphthoic acid, constituent units derived from aromatic diols, constituent units derived from terephthalic acid and constituent units derived from 2,6-naphthalene dicarboxylic acid, and further preferably has all of the constituent units selected from the group consisting of constituent units derived from 6-hydroxy-2-naphthoic acid, constituent units derived from aromatic diols, constituent units derived from terephthalic acid and constituent units derived from 2,6-naphthalene dicarboxylic acid.

[0061] The synthesis method of thermoplastic liquid crystal polyester is not particularly limited, and can be synthesized by polymerizing the above-mentioned compounds by known methods such as melt polymerization, solid phase polymerization, solution polymerization and slurry polymerization. As thermoplastic liquid crystal polyester, commercially available products can be used. As commercially available products of thermoplastic liquid crystal polyester, for example: "LAPEROS" made by Polyplastics, "VECTRA" made by Celanese, "UENOLCP" made by Ueno Pharmaceutical, "SUMIKA SUPER LCP" made by Sumitomo Chemical, "XYDAR" made by ENEOS, and "SIVERAS" made by Toray Industries, Inc. can be cited. It should be noted that the thermoplastic liquid crystal polyester can form a chemical bond with a cross-linking agent or a compatible component (reactive compatibilizer) as an optional component.

[0062] The melting point (Tm) of the thermoplastic liquid crystal polyester is above 250°C. When the melting point is lower than 250°C, the reflow soldering property is poor, so when used for printed circuit boards and the like, the processing method is limited. The melting point of the thermoplastic liquid crystal polyester is not particularly limited. From the viewpoints of heat resistance and molding processability, for example, it is preferably below 400°C, more preferably below 350°C, further preferably below 330°C, and particularly preferably below 300°C. The lower limit of the melting point is more preferably above 260°C, and more preferably above 270°C. It should be noted that the melting point of the thermoplastic liquid crystal polyester can be determined by a conventionally known method, for example, a differential scanning calorimeter (DSC) is used to heat the sample at a heating rate of 10°C / min to completely melt it, and then the melt is cooled to 30°C at a cooling rate of 10°C / min, and the top of the endothermic peak that appears when the temperature is increased at a heating rate of 10°C / min is taken as the melting point.

[0063] [Amorphous copolyester]

[0064] As a preferred embodiment, the liquid crystal polyester film of the present invention may also contain amorphous copolyesters in addition to the above-mentioned thermoplastic liquid crystal polyester. The liquid crystal polyester film containing amorphous copolyesters in addition to the above-mentioned thermoplastic liquid crystal polyester has excellent slip properties near the crystallization temperature. Amorphous copolyesters are polycondensates of polycarboxylic acids and polyols, and do not have a clear endothermic peak in a thermal analysis measurement using differential scanning calorimetry (DSC). For example, in a thermal analysis measurement using DSC, it only has a step-like endothermic change, is solid at room temperature, and is thermoplasticized at a temperature above the glass transition temperature.

[0065] The amorphous copolyester preferably contains constituent units derived from terephthalic acid monomers and constituent units derived from 1,4-cyclohexanedimethanol. The terephthalic acid monomers are terephthalic acid or derivatives of terephthalic acid. As derivatives of terephthalic acid, for example, halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides, and mixtures thereof of terephthalic acid can be cited. As derivatives of terephthalic acid, for example, dialkyl esters and diaryl esters of terephthalic acid can be cited, and specific examples thereof include dimethyl terephthalate (DMT) and diethyl terephthalate.

[0066] Amorphous copolyesters may also contain constituent units from other monomers. In one embodiment, constituent units from dicarboxylic acids (other dicarboxylic acids) other than terephthalic acid monomers are also included. As other dicarboxylic acids, for example: cyclohexane dicarboxylic acid, isophthalic acid, naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, distyrene dicarboxylic acid, etc. As cyclohexane dicarboxylic acids, 1,3- and / or 1,4-cyclohexane dicarboxylic acids, etc., may be mentioned. In the case where the amorphous copolyester contains constituent units from other dicarboxylic acids, the content ratio of the constituent units from terephthalic acid monomers relative to the total amount of dicarboxylic acids (the total amount of constituent units from terephthalic acid monomers and constituent units from other dicarboxylic acids) is preferably 40 mol% or more, more preferably 40 mol% to 90 mol%, and further preferably 50 mol% to 85 mol%.

[0067] The amorphous copolyester may also include constituent units from diols (other diols) other than 1,4-cyclohexanedimethanol. As other diols, for example, aliphatic or alicyclic diols (preferably having 2 to 20 carbon atoms) may be cited. As other diols, for example, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, etc. may be cited. In one embodiment, the amorphous copolyester also includes constituent units from 2,2,4,4-tetramethyl-1,3-cyclobutanediol. In the case where the amorphous copolymer contains a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), the content ratio of the constituent unit derived from 1,4-cyclohexanedimethanol (CHDM) is preferably 10 mol% to 90 mol% relative to the total of the constituent unit derived from TMCD and the constituent unit derived from CHDM, more preferably 20 mol% to 85 mol%, and further preferably 30 mol% to 80 mol%. In addition, the content ratio of the constituent unit derived from TMCD is preferably 10 mol% to 90 mol% relative to the total of the constituent unit derived from TMCD and the constituent unit derived from CHDM, more preferably 15 mol% to 80 mol%, and further preferably 20 mol% to 70 mol%.

[0068] The glass transition temperature (Tg) of the amorphous copolyester is 80°C to 200°C, preferably 85°C to 180°C, more preferably 90°C to 160°C, further preferably 95°C to 150°C, and particularly preferably 100°C to 140°C. It should be noted that the glass transition temperature can be measured by a conventionally known method, for example, it can be obtained by differential scanning calorimetry in accordance with JISK-7121:2012. In addition, regarding the glass transition temperature, when there is a published value of the manufacturer, the published value of the manufacturer can be used.

[0069] In the case where the liquid crystal polyester film of the present invention includes an amorphous copolyester, the mixing ratio of the thermoplastic liquid crystal polyester (A) and the amorphous copolyester (B) is preferably (A): (B) = 50~99.5 wt %: 0.5~50 wt %. More preferably, (A): (B) = 70~99 wt %: 1~30 wt %, further preferably (A): (B) = 85~98 wt %: 2~15 wt %, and particularly preferably (A): (B) = 90~97.5 wt %: 2.5~10 wt %. When the mixing amount of the amorphous copolyester is less than the above range, the effect of improving the slip properties of the liquid crystal polyester film near the crystallization temperature is lacking, and it may be difficult to obtain a smooth film by manufacturing a processed film using a blow extrusion molding method. When the mixing amount of the amorphous copolyester is more than the above range, the heat resistance and mechanical properties of the liquid crystal polyester film may be reduced.

[0070] The liquid crystal polyester film of the present invention may contain other resin components other than the above-mentioned thermoplastic liquid crystal polyester and amorphous copolyester within the range that does not impair the effect of the present invention. As other resin components, thermoplastic resins such as polyarylate, polyphenylene sulfide, polyphenylene ether, polyetheretherketone, polyetherimide, cycloolefin polymer, polyamide, polyamideimide, polyimide, epoxy-containing olefin copolymer, styrene resin, copolyester elastomer can be cited. In addition, the liquid crystal polyester film of the present invention may also contain additives such as a compatibilizer, a lubricant, and an antioxidant.

[0071] The liquid crystal polyester film of the present invention may contain inorganic particles and organic particles as reinforcing materials, cushion materials, materials for improving dielectric constant and dielectric loss tangent, and materials for improving sliding properties. As inorganic particles, there are: silicon dioxide, titanium oxide, barium sulfate, talc, zirconium oxide, aluminum oxide, silicon nitride, silicon carbide, calcium carbonate, silicate, glass beads, graphite, tungsten carbide, carbon black, clay, mica, carbon fiber, glass fiber, metal powder, etc. As organic particles, there are: cross-linked acrylic beads, cross-linked ethylene beads, etc. The content of inorganic particles and organic particles is 0 to 40 weight % relative to the total mass of the liquid crystal polyester film.

[0072] [Method for producing liquid crystal polyester film]

[0073] The method for producing the liquid crystal polyester film of the present invention is not particularly limited as long as it is a method that can produce a smooth film without sagging or wrinkles, but a blown film produced by a blown extrusion molding method is preferred.

[0074] When the components constituting the liquid crystal polyester film include other components such as thermoplastic liquid crystal polyester and amorphous copolyester, in order to provide a stable mixing state, melt mixing is performed before film formation, and preferably granulation is performed in advance. The equipment used for melt mixing is not particularly limited, and examples thereof include: various well-known extruders such as intermittent mixers, kneaders, co-kneaders, Banbury mixers, roll mills, single-screw or twin-screw extruders. Among them, single-screw extruders and twin-screw extruders are preferably used from the perspective of excellent mixing capacity and productivity.

[0075] As blow extrusion molding, for example, the following method can be cited: the above-mentioned resin composition is provided to a melt extruder having a die head with an annular slit, and the molten resin composition is extruded upward or downward from the annular slit of the extruder into a bubble shape, and air or an inert gas is blown into the inside of the bubble composed of the molten resin composition, thereby expanding and stretching the bubble in a direction (TD direction) at right angles to the flow direction (MD direction) to obtain a film. The barrel temperature of the melt extruder is usually 260~400°C, preferably 280~380°C. The interval of the annular slit is usually 0.1~5mm, preferably 0.2~2mm. The diameter of the annular slit is usually 20~1000mm, preferably 25~600mm.

[0076] In blow extrusion molding, the blow ratio is preferably 1.5 or more, more preferably 2.0 or more, further preferably 4.0 or more, and particularly preferably 4.5 or more. The upper limit of the blow ratio is not particularly limited, for example, the blow ratio is 10 or less. In addition, the draft ratio is preferably 1.5 or more and 20 or less, more preferably 1.5 or more and 10 or less. Among them, the blow ratio is the stretching ratio in the TD direction, and the draft ratio is the stretching ratio in the MD direction. When the blow ratio and the draft ratio are within the above range, the anisotropy of the tensile modulus and the tensile strength of the obtained film (the difference between the MD direction and the TD direction) can be improved.

[0077] The liquid crystal polyester film of the present invention can be further heat treated to relax the orientation of the molecular chains and improve the film dimensional stability. The heat treatment can be performed by a conventionally known method, such as contact heat treatment, non-contact heat treatment, etc., and the type of heat treatment is not particularly limited.

[0078] [Metallic Laminated Film]

[0079] The liquid crystal polyester film of the present invention can be used as a metal laminate film by laminating a metal layer thereon. When laminating the metal layer, the surface of the liquid crystal polyester film on which the metal layer is laminated can be subjected to corona discharge treatment, ultraviolet irradiation treatment or plasma treatment in order to improve the adhesive force.

[0080] As a method for laminating a metal layer on the liquid crystal polyester film of the present invention, for example: (1) a method of attaching the liquid crystal polyester film to a metal foil by heating and pressing; (2) a method of attaching the liquid crystal polyester film and the metal foil by an adhesive; (3) a method of forming a metal layer on the liquid crystal polyester film by vapor deposition. Among them, the lamination method (1) is a method of pressing the liquid crystal polyester film with the metal foil near the flow starting temperature using a punch or a heating roller, which is recommended because it is easy to implement. As an adhesive used in the lamination method (2), for example: hot melt adhesive, polyurethane adhesive. Among them, it is preferred to use an epoxy-containing ethylene copolymer as the adhesive. As a lamination method (3), for example: ion beam sputtering method, high frequency sputtering method, DC magnetron sputtering method, glow discharge method. Among them, it is preferred to use a high frequency sputtering method.

[0081] As the metal used in the metal layer, for example, gold, silver, copper, copper alloy, nickel, nickel alloy, aluminum, aluminum alloy, iron, iron alloy, etc. can be cited. In label tapes and circuit substrate applications, copper is preferred, and in capacitor applications, aluminum is preferred. As the structure of the metal laminated film thus obtained, for example, a two-layer structure of a liquid crystal polyester film and a metal layer, a three-layer structure formed by laminating metal layers on both sides of a liquid crystal polyester film, and a five-layer structure formed by alternately laminating liquid crystal polyester films and metal layers can be cited. It should be noted that in order to show high strength, the laminate can be heat treated as needed. The thickness of the metal layer is not particularly limited, for example, preferably 1.5~1000μm, more preferably 2~500μm, further preferably 5~150μm, and particularly preferably 7~100μm. When thinner than this range, the mechanical strength is poor, and when thicker than the above range, the operability and processability are poor.

[0082] The circuit substrate of the present invention comprises at least one conductor layer and at least one insulator (or dielectric) layer. As long as the liquid crystal polyester film of the present invention is used as an insulator (or dielectric), its form is not particularly limited and can be used as various high-frequency circuit substrates in a known or commonly used manner. In addition, the circuit substrate can be a circuit substrate (or semiconductor element mounting substrate) equipped with a semiconductor element (e.g., IC chip).

[0083] The conductor layer used in the circuit substrate of the present invention is formed of at least a conductive metal, and a circuit pattern is formed on the conductor layer using a known circuit processing method. The conductor forming the conductor layer can be various conductive metals, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof. In addition, the circuit pattern can be formed on the metal layer portion of the above-mentioned metal laminate film.

[0084] Example

[0085] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.

[0086] As the resin used in the examples and comparative examples, the following resin was used. (Thermoplastic liquid crystal polyester)

[0087] ・LCP (1): A thermoplastic liquid crystal polyester composed of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid (LAPEROS A950RX manufactured by Polyplastics Co., Ltd., melting point: 280°C, crystallization temperature: 235°C)

[0088] ・LCP (2): A thermoplastic liquid crystal polyester composed of a structural unit derived from p-hydroxybenzoic acid, a structural unit derived from 6-hydroxy-2-naphthoic acid, and a structural unit derived from terephthalic acid (LAPEROS C950RX manufactured by Polyplastics Co., Ltd., melting point: 320°C, crystallization temperature: 285°C)

[0089] (Amorphous polymer)

[0090] ・Amorphous polymer (1): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX2001 manufactured by Eastman Chemical Company, Tg: 116°C)

[0091] ・Amorphous polymer (2): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX1001 manufactured by Eastman Chemical Company, Tg: 108°C)

[0092] ・Amorphous polymer (3): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from ethylene glycol (PCTG DN011 manufactured by Eastman Chemical Company, Tg: 90°C)

[0093] ・Amorphous polymer (4): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from isophthalic acid (PCTA AN004 manufactured by Eastman Chemical Company, Tg: 90°C)

[0094] ・Amorphous polymer (5): polyarylate resin (U Polymer U-100 manufactured by Unitika Co., Ltd., Tg: 193°C)

[0095] ・Amorphous polymer (6): Polysulfone resin (Ultrason S3010 manufactured by BASF, Tg: 187°C)

[0096] (additive)

[0097] ・Polyester elastomer: Block copolymer of polybutylene terephthalate and polybutylene glycol (PBT / PTMG)

[0098] It should be noted that the crystallization temperature is the top of the exothermic peak obtained by using a differential scanning calorimeter (DSC) to raise the temperature from room temperature to 320-380°C at a heating rate of 10°C / min to completely melt the thermoplastic liquid crystal polyester and then cooling the temperature to 30°C at a cooling rate of 10°C / min as the crystallization temperature.

[0099] The glass transition temperature used was the manufacturer's catalog value.

[0100] (Film production by blow extrusion)

[0101] After premixing the thermoplastic liquid crystal polyester and the like according to the ratio described in Table 1, the mixture was heated and kneaded by a single screw extruder, and melt-extruded into bubbles at a discharge rate of 3 kg / h from an annular blow molding die head (diameter 25 mm), and the bubbles were stretched under the conditions of draft ratio = 2 and blow ratio = 5, and a liquid crystal polyester film with a thickness of 50 μm was obtained by blow extrusion molding. The resin temperature of the bubbles during film formation was controlled so that the temperature from the contact position with the stabilizing plate to the pinch roller was above the crystallization temperature. The physical properties and appearance of the film obtained by the following evaluation method are shown in Table 1.

[0102] (Physical properties: dynamic friction coefficient)

[0103] use Figure 1 The measurement device shown is based on JIS K7125-1999, and the measurement is performed by the following method. Figure 1 It is a simplified schematic diagram of a measuring device for the dynamic friction coefficient in the present invention. Figure 1The measuring device shown is equipped with a load cell 1 (Autograph AGS-500NX, manufactured by Shimadzu Corporation), a pulley 2, a slider 3 (the bottom surface of which is covered with a fluorofiber woven fabric (manufactured by Toray Industries, Inc., model: Toyoflon #406W), size: length 63 mm × width 63 mm), a slider total mass 4 (200 g = vertical load 1.96 N), a sample 5 (size: length 80 mm × width 200 mm), and a hot plate (table) 6 (manufactured by ASONE, model: CREAMICHOTPLATECHP-1700) with a temperature control function. The sample is the film obtained above, cut into a rectangular shape in such a way that the long side is parallel to the MD direction of the film, and placed in such a way that the MD direction of the film is parallel to the sliding direction. Then, the temperature of the hot plate is adjusted, and the slider 3 and the sample 5 are relatively moved at a measuring speed of 100 mm / min, so as to measure the dynamic friction coefficient between the surfaces of the slider 3 and the sample 5 at each temperature. The measurement is performed 3 times at each temperature, and the average value thereof is taken as the dynamic friction coefficient.

[0104] The coefficient of dynamic friction was calculated by the following method based on the following formula: The dynamic friction force (FD) is the average value of the first 6 cm after the relative deviation movement between the contact surfaces starts, ignoring the peak of the static friction force.

[0105] μD=FD / Fp

[0106] μD: Dynamic friction coefficient

[0107] FD: Dynamic friction (N)

[0108] Fp: Normal force generated by the mass of the sliding part (=1.96N)

[0109] (Physical properties: Crystallization temperature)

[0110] Using a differential scanning calorimeter (DSC), the temperature was raised from room temperature to 320-380°C at a rate of 10°C / min to completely melt the film, and then the temperature was lowered to 30°C at a rate of 10°C / min to measure the crystallization temperature.

[0111] (Appearance: Wrinkles on the membrane)

[0112] The obtained film was visually evaluated for sag and wrinkles in the TD direction (transverse wrinkles) according to the following criteria.

[0113] ○: No slack or wrinkles were observed on the film, or slight wrinkles were observed on the film;

[0114] △: Multiple faint wrinkles and significant wrinkles are visible on the film, and sagging is also visible;

[0115] ×: Many significant wrinkles were observed on the film, and sagging was observed.

[0116] [Table 1]

[0117]

[0118] As shown in Table 1, the dynamic friction coefficient (μ D1 ) is less than 0.25, or the dynamic friction coefficient ratio (μ D1 / μ D2 The liquid crystal polyester films of Examples 1 to 7 in which the ratio ) is 1.25 or less are excellent in mechanical properties, electrical properties, etc., and are smooth films without sagging or wrinkles.

[0119] On the other hand, the dynamic friction coefficient (μ D1 ) exceeds 0.25, or the dynamic friction coefficient ratio (μ D1 / μ D2 ) exceeded 1.25 in the liquid crystal polyester films of Comparative Examples 1 to 3, film sag and horizontal wrinkles occurred, and a smooth film could not be obtained. As shown in the results, in order to obtain a smooth liquid crystal polyester film in which film sag and wrinkles are suppressed during extrusion molding such as blow extrusion molding, it is important to reduce the dynamic friction coefficient near the crystallization temperature and reduce the change in the dynamic friction coefficient near the crystallization temperature.

[0120] Industrial Applicability

[0121] As described above, the liquid crystal polyester film obtained by the present invention is also used for electrical insulation of motor transformers, element formation film of flexible solar cells, etc., by utilizing its excellent mechanical properties, electrical properties, dimensional stability, and heat resistance. In addition, it is also used in the acoustic field such as surface protection films and vibration plates.

[0122] The metal laminate film of the present invention can also be used for circuit substrates, capacitors, electromagnetic shielding materials, etc. The circuit substrate of the present invention can be used for various transmission lines and antennas (for example, microwave or millimeter wave antennas), and can also be used for antenna devices integrating antennas and transmission lines.

Claims

1. A liquid crystal polyester film, characterized in that: The main component of the thermoplastic liquid crystal polyester is a crystallization temperature Tc of 180°C or higher and 320°C or lower, and the dynamic friction coefficient μ at the crystallization temperature Tc+5°C is D1 Less than 0.

25.

2. A liquid crystal polyester film, characterized in that: The main component of the thermoplastic liquid crystal polyester is a crystallization temperature Tc of 180°C or higher and 320°C or lower, and the dynamic friction coefficient μ at the crystallization temperature Tc+5°C is D1 The dynamic friction coefficient μ at the crystallization temperature Tc-5°C D2 The dynamic friction coefficient is μ D1 / μ D2 Below 1.

25.

3. The liquid crystal polyester film according to claim 1 or 2, characterized in that: The thermoplastic liquid crystal polyester includes at least one selected from the group consisting of constituent units derived from p-hydroxybenzoic acid and constituent units derived from 6-hydroxy-2-naphthoic acid.

4. The liquid crystal polyester film according to claim 1 or 2, characterized in that: The crystallization temperature Tc is 220° C. or higher and 300° C. or lower.

5. The liquid crystal polyester film according to claim 1 or 2, characterized in that: The present invention contains an amorphous copolyester having a glass transition temperature of 80° C. to 200° C.

6. The liquid crystal polyester film according to claim 5, characterized in that: The amorphous copolyester includes a constituent unit derived from a terephthalic acid-based monomer and a constituent unit derived from 1,4-cyclohexanedimethanol.

7. The liquid crystal polyester film according to claim 1 or 2, characterized in that: The liquid crystal polyester film is a blown film.

8. A metal laminate film, characterized in that: A metal layer is laminated on one or both sides of the liquid crystal polyester film according to claim 1 or 2. 9 . A circuit board comprising at least one conductor layer and the liquid crystal polyester film according to claim 1 or 2 .

Citation Information

Patent Citations

  • Inflation film forming method and apparatus therefor

    JP2002240146A